2017
DOI: 10.21037/jtd.2017.03.174
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of postoperative thoracic radiotherapy for small cell lung cancer subdivided by lymph node stage: a systematic review and meta-analysis

Abstract: This is the first meta-analysis of the benefits of PORT for SCLC patients. Although derived from retrospective cohort studies, the data showed that PORT significantly reduced the risk of recurrence and improved survival for patients with pN2-SCLC; however, patients with pN0-SCLC did not benefit from PORT, whereas for patients with pN1-SCLC, PORT reduced the LRR rates and improved the 1-year survival rate. The long-term survival benefits of PORT remain unclear and will require further prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Radiation therapy has been widely used since 1992. However, accumulating evidence has revealed that radiotherapy resistance is usually acquired soon after the treatment, and the corresponding additional irradiation dose often leads to unacceptable toxicity [ 24 , 25 ]. It is urgent for researchers to identify the regulatory mechanism for the metastasis of SCLC cells and reveal the molecular mechanisms underlying acquired radiotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy has been widely used since 1992. However, accumulating evidence has revealed that radiotherapy resistance is usually acquired soon after the treatment, and the corresponding additional irradiation dose often leads to unacceptable toxicity [ 24 , 25 ]. It is urgent for researchers to identify the regulatory mechanism for the metastasis of SCLC cells and reveal the molecular mechanisms underlying acquired radiotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the exact definition of R0 resection could be substantially complemented with negative results of assays for postoperative detection of circulating tumor cells or DNA in the near future 198 . Importantly, in case of nodal upstaging (N1 or N2) or incomplete surgical resection (i.e., R1), adjuvant chemotherapy should be complemented with thoracic radiotherapy 199,200 . In this setting, postoperative thoracic radiotherapy significantly decreases the 1‐year, 2‐year, and 3‐year local recurrence rates in patients with nodal involvement (i.e., N1 and N2) 199 .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Importantly, in case of nodal upstaging (N1 or N2) or incomplete surgical resection (i.e., R1), adjuvant chemotherapy should be complemented with thoracic radiotherapy 199,200 . In this setting, postoperative thoracic radiotherapy significantly decreases the 1‐year, 2‐year, and 3‐year local recurrence rates in patients with nodal involvement (i.e., N1 and N2) 199 . Postoperative prophylactic cranial irradiation (PCI) has been shown to significantly reduce the risk of brain metastasis and prolong OS in patients who undergo surgery for SCLC 201,202 .…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…PORT can improve 5-year OS in pN2 disease[ 94 - 96 ], but does not significantly improve OS in stage pN1[ 75 ]. A MTA[ 97 ] concluded that PORT improves 1-3 year LC rates in pN1 and pN2 and 1-5 year OS in pN2 disease. However, PORT provides no benefit in pN0[ 98 , 99 ].…”
Section: Definition Of Volumes and Organs At Riskmentioning
confidence: 99%